A8.7 Hydrogen sulfide treatment reduces joint degradation in autoimmune arthritis. (13th February 2015) - Sieghart, D; Saferding, V; Goncalves-Alves, E; Koenders, MI; Blüml, S; Steiner, G
Abstract : Background and objectives: The gasotransmitter hydrogen sulfide (H2 S) has been demonstrated to exert anti-inflammatory effects on different types of cells important in the pathogenesis of rheumatoid arthritis (RA) and osteoarthritis such as monocytes/macrophages, synovial fibroblasts or chondrocytes. It was the aim of this study to investigate whether treatment with the H2 S donor sodium hydrogen sulfide (NaHS) may influence disease development and outcome of experimental RA. Materials and methods: In a first series of experiments NaHS was applied three times a week to healthy mice. Two hours before the end of the experiment, mice were challenged with LPS or PBS as negative control. Collagen-induced arthritis (CIA) was induced by a dual injection of bovine collagen type II. NaHS was applied two times before the first collagen injection and six times between the first collagen injection and the boost. On day 57 the experiment was terminated and blood, spleen, lymph nodes and paws were analysed in detail. Serum transfer arthritis was induced in C57BL/6 mice by two i.p. injections (day 0 and 2) of arthritogenic serum from K/BxN mice and NaHS was applied on days -1, 1, 3, 6 and 8. The experiment was terminated on day 9 and blood, spleen and paws were collected. Results: LPS challenged mice treated with 0.4 mM NaHS had reduced serum levels of TNF-α, IL-4 and IL-23 compared to placebo treated animals without showing clinical symptoms of intoxication. In both disease models NaHS treatment did not influence clinical signs of arthritis such as paw swelling and grip strength. However, histological evaluation of affected paws revealed significant reduction of joint degradation in mice with serum transfer arthritis with reduced inflammation and cartilage loss and almost complete absence of bone erosion and osteoclasts. In contrast, NaHS treatment during the preclinical phase did not influence histological parameters in mice with CIA. Conclusions: Our investigations in the serum transfer arthritis model which largely reflects the effector phase of arthritis involving mainly the innate immune system showed highly reduced joint degradation and almost complete inhibition of bone erosion in NaHS treated mice. This is in line with recently published data demonstrating that NaHS inhibits osteoclastogenesis, both in murine bone marrow cells 1 and human CD11b+ cells. 2 References: Lee et al . J Cell Biochem 2013; 114 :1183–93. Gambari L, Lisignoli G, Cattini L, et al . Pharmacol Res 2014; 87 :99–112.